2020
DOI: 10.1155/2020/2048210
|View full text |Cite
|
Sign up to set email alerts
|

SMARCB1 Promotes Ubiquitination and Degradation of NR4A3 via Direct Interaction Driven by ROS in Vascular Endothelial Cell Injury

Abstract: Nuclear receptor subfamily 4 group A member 3 (NR4A3) protects the vascular endothelial cell (VEC) against hypoxia stress, whose expression is primarily reported to be governed at a transcriptional level. However, the regulation of NR4A3 in the protein level is largely unknown. Here, we report that NR4A3 protein abundance is decreased immensely in VEC injury induced by reoxygenation after oxygen-glucose deprivation (OGD-R), which is significantly blocked by the administration of the antioxidative steroid TRIOL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…This pro-survival effect is triggered, at least in a part, by the NOR-1-dependent induction of cIAP2 (cellular inhibitor of apoptosis 2) [ 32 , 34 ], an anti-apoptotic protein whose transcriptional activity is regulated by NOR-1 through a NBRE [ 34 ]. Recent studies have revealed that NOR-1 activity is also modulated by post-translational mechanisms [ 110 ]. NOR-1 protein levels were dramatically decreased in endothelial cells subjected to reoxygenation after oxygen–glucose deprivation.…”
Section: The Nr4a Subfamily Of Nrsmentioning
confidence: 99%
See 1 more Smart Citation
“…This pro-survival effect is triggered, at least in a part, by the NOR-1-dependent induction of cIAP2 (cellular inhibitor of apoptosis 2) [ 32 , 34 ], an anti-apoptotic protein whose transcriptional activity is regulated by NOR-1 through a NBRE [ 34 ]. Recent studies have revealed that NOR-1 activity is also modulated by post-translational mechanisms [ 110 ]. NOR-1 protein levels were dramatically decreased in endothelial cells subjected to reoxygenation after oxygen–glucose deprivation.…”
Section: The Nr4a Subfamily Of Nrsmentioning
confidence: 99%
“…The effect was blocked by the antioxidant TRIOL, which ameliorated endothelial hyperpermeability provoked by acute hypobaric hypoxia in vivo. The mechanism involves ROS-driven ubiquitination and degradation of NOR-1 promoted by SMARCB1 (SWI/SNF related, matrix associated, actin dependent regulator of chromatin, subfamily B, member 1) [ 110 ]. The authors highlighted the potential usefulness of these findings to design strategies that improve pulmonary endothelial barrier in acute lung injury.…”
Section: The Nr4a Subfamily Of Nrsmentioning
confidence: 99%
“…et al discovered an upregulation of monocarboxylate transporter 4 (MCT4), induced by OGD/R, facilitating a shift towards glycolysis by regulating LDHA and suppressing oxidative phosphorylation (OXPHOS), ultimately contributing to cardiac protection in myocardial ischemia/reperfusion (I/R) injury[60]. Additionally, Lu B et al revealed that reoxygenationinduced vascular endothelial cell (VEC) injury resulted in a significant reduction in the protein abundance of NR4A3, and the antioxidant steroid TRIOL countered this effect by inhibiting ROSdriven ubiquitination and degradation[61]. This highlights a novel post-translational regulation involving the interaction between NR4A3 and SMARCB1 in vascular endothelial cells.…”
mentioning
confidence: 99%